1995
DOI: 10.1038/377209a0
|View full text |Cite
|
Sign up to set email alerts
|

Transcription complex stability and chromatin dynamics in vivo

Abstract: Distant regulatory sequences affect transcription through long-range chromatin interactions. Visualization of transcriptional activity of genes that compete for distant elements, using the globin locus as a model, has revealed the dynamics of chromatin interactions in vivo. Multiple genes appear to be transcribed alternately rather than at the same time to generate several messenger RNAs in one cell. The regulator may stably complex with one gene at a time and switch back and forth between genes in a flip-flop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
354
1
9

Year Published

1997
1997
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(402 citation statements)
references
References 35 publications
38
354
1
9
Order By: Relevance
“…It is also possible that each cell expresses both genes from the mutant paternal allele but only one gene is expressed at a given time. The latter is analogous to the flip-flop model of gene regulation that has been proposed to explain how distal control elements allow the simultaneous expression of ␥-and ␤-globin in early development (Wijgerde et al 1995). Future studies of our mutants at the cellular level will discriminate between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that each cell expresses both genes from the mutant paternal allele but only one gene is expressed at a given time. The latter is analogous to the flip-flop model of gene regulation that has been proposed to explain how distal control elements allow the simultaneous expression of ␥-and ␤-globin in early development (Wijgerde et al 1995). Future studies of our mutants at the cellular level will discriminate between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Probes were labeled with dinitrophenol, digoxygenin, or biotin. The oligonucleotide intron probes were as described by Wijgerde et al (1995). After hybridization, the coverslips were removed by dipping in 2× SSC, and the slides were washed three times in 2× SSC at 37°C, followed by a 5-min wash in 0.1 M Tris, …”
Section: Rnase Protectionmentioning
confidence: 99%
“…This analysis was performed as described previously (Wijgerde et al 1995). Fetal livers (13.5 day) were disrupted in PBS, and the cells were fixed onto poly-L-lysine-coated slides with 4% formaldehyde/5% acetic acid in normal saline for 20 min at room temperature.…”
Section: Rnase Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of a dynamic equilibrium between the active and the inactive state of a gene locus, which (in the case of transgenes) is a function of the genomic integration site, is supported by a variety of studies. In a series of elegant experiments, Fraser and co-workers (27) have demonstrated that the human ␤-globin LCR-promoter interaction is dynamic and switches between several promoters of the downstream located globin genes (25). The authors also analyzed certain transgenic mouse lines carrying deletion mutants of the complete ␤-globin locus, which render the transgene susceptible to genomic position effects.…”
Section: Incomplete Gene Loci Do Not Form Stable Transcription Complexesmentioning
confidence: 99%